54.4k views
5 votes
Marta is solving the equation S = 2πrh + 2πr2 for h. Which should be the result?

2 Answers

3 votes

Answer:

A)
h =(s)/(2\pi r) -r

Explanation:


s = 2\pi rh + 2\pi r^2


s = 2\pi r (h + r)\\h + r =(s)/(2\pi r) \\h =(s)/(2\pi r) -r

User Derenio
by
5.0k points
4 votes

Answer:

h = S - 2πr² /2πr

Explanation:

Marta is solving the equation S = 2πrh + 2πr2 for h. Which should be the result?

To solve;

S = 2πrh + 2πr²

The first thing to do is to subtract 2πr² from both-side of the equation

S - 2πr² = 2πrh + 2πr² - 2πr²

S - 2πr² = 2πrh

Then next is to divide both-side of the equation by 2πr

S - 2πr² / 2πr = 2πrh /2πr

On the right-hand side of the equation 2πr at the numerator will cancel-out 2πr at the denominator, leaving us with just h while on the left-hand side of the equation S-2πr² will be divided by 2πr)

S - 2πr² / 2πr = h

Therefore the result should be h = S - 2πr² / 2πr

User Ahmad Ali
by
5.1k points